2019
DOI: 10.3389/fpls.2019.00103
|View full text |Cite
|
Sign up to set email alerts
|

Water-Use Efficiency: Advances and Challenges in a Changing Climate

Abstract: Water use efficiency (WUE) is defined as the amount of carbon assimilated as biomass or grain produced per unit of water used by the crop. One of the primary questions being asked is how plants will respond to a changing climate with changes in temperature, precipitation, and carbon dioxide (CO 2 ) that affect their WUE At the leaf level, increasing CO 2 increases WUE until the leaf is exposed to temperatures exceeded the optimum for growth (i.e., heat stress) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
366
1
12

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 648 publications
(395 citation statements)
references
References 130 publications
16
366
1
12
Order By: Relevance
“…Ritchie (1972) reported that canopy development and growth affect transpiration, which increases linearly with leaf area. However, row spacing of a crop would affect the partitioning of the ET by reducing the soil water evaporation and increasing canopy transpiration in a monoculture (Hatfield & Dold, 2019). Nevertheless, deeply rooted crops increase the contribution of transpiration to ET even in semiarid and arid environments (Kizito, Dragila, & Sene, 2006), which mainly drives total ET.…”
Section: Evapotranspirationmentioning
confidence: 99%
“…Ritchie (1972) reported that canopy development and growth affect transpiration, which increases linearly with leaf area. However, row spacing of a crop would affect the partitioning of the ET by reducing the soil water evaporation and increasing canopy transpiration in a monoculture (Hatfield & Dold, 2019). Nevertheless, deeply rooted crops increase the contribution of transpiration to ET even in semiarid and arid environments (Kizito, Dragila, & Sene, 2006), which mainly drives total ET.…”
Section: Evapotranspirationmentioning
confidence: 99%
“…The change in the air temperature surrounding the leaf will change the leaf temperature and directly affect the gradient of water vapor between the leaf and the atmosphere. Water deficit stress and heat stress may be induced by changes in available water, VPD, and increased ambient air temperature [65].…”
Section: Discussionmentioning
confidence: 99%
“…We were also interested to find a possible association between capability to fix nitrogen and efficiency to use water (WUE), which increases under drought (Hatfield & Dold, ). WUE is defined as the amount of carbon assimilated as biomass or grain produced per unit of water used by a crop.…”
Section: Discussionmentioning
confidence: 99%
“…However, we still have to find out whether better drought tolerance of BAT 477 solely depends on a more favorable root angle or whether this line has simply more roots and therefore accesses more water, which in turn would permit more N-fixation. We were also interested to find a possible association between capability to fix nitrogen and efficiency to use water (WUE), which increases under drought (Hatfield & Dold, 2019). WUE is defined as the amount of carbon assimilated as biomass or grain produced per unit of water used by a crop.…”
Section: Discussionmentioning
confidence: 99%